DAMPAK PENERAPAN KURIKULUM KKNI PADA PERKULIAHAN PRODI TATA RIAS AKS-AKK - Pambudi, Ika Prasetyani (Jurnal Socia Akademika, 2025)
The increasingly competitive demands of the workforce require vocational education to implement competency-based curricula that are relevant to industry needs. This study aims to examine the impact of implementing the KKNI curriculum on the learning process of the Beauty and Makeup Study Program at AKS-AKK. This research is a qualitative study using a descriptive method. Data collection was carried out through in-depth interviews, observations, and documentation studies involving lecturers, students, and curriculum documents of the Beauty and Makeup Study Program, and was analyzed qualitatively. The findings show that the implementation of the KKNI curriculum in the Beauty and Makeup Program at AKS-AKK has had a positive impact on improving the quality of vocational education. The curriculum has encouraged a more structured learning process based on learning outcomes and aligned with the needs of the beauty industry. The study revealed improved graduate competencies in terms of knowledge, technical skills, and professional attitudes. Moreover, the implementation of KKNI has also strengthened collaboration with industry as well as the integration of education, research, and community service. These findings affirm that KKNI plays a strategic role in producing adaptive, competent, and globally competitive graduates in the field of beauty and makeup